Pengaruh Terapi Murottal terhadap Tingkat Kecemasan pada Ibu Hamil Trimester III di Desa Tawang Rejeni Kecamatan Turen - Lilik Farihatul Mufarrohah; Tut Rahyani A. W (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The third trimester of pregnancy is a period highly vulnerable to anxiety, as expectant mothers begin to face fears related to the labor process and the safety of their babies. If left unaddressed, this anxiety can negatively impact both maternal and fetal health. Murottal therapy, which involves listening to rhythmic recitations of the Holy Qur'an, is a non-pharmacological approach considered effective in reducing anxiety through its relaxing and spiritually calming effects. This study aims to determine the effect of murottal therapy on anxiety levels among third-trimester pregnant women in Tawangrejeni Village, Turen District. The method used is descriptive quantitative with a comparative design involving two groups: intervention and control, each consisting of 20 respondents selected through total sampling. A Guttman-scale questionnaire was used to assess anxiety levels. Data analysis using the Mann-Whitney U test showed a significant result (p = 0.000), indicating that murottal therapy had a significant effect in reducing anxiety in pregnant women. Therefore, murottal therapy can be considered a simple, low-cost, and culturally appropriate non-pharmacological alternative for addressing anxiety, especially in primary healthcare settings such as community health posts (posyandu).